Pinched between the plates: Armenia's voluminous record of volcanic activity. (18th June 2020) - Halama, Ralf; Meliksetian, Khachatur; Savov, Ivan P.; Sugden, Patrick J.; Sokół, Krzysztof
Abstract : Located in the heart of the Lesser Caucasus mountains, where the Arabian and Eurasian tectonic plates collide, Armenia occupies an exceptional geological position shaped through millions of years of subduction and collision. It is a unique place on the Earth recording extensive intrusive and volcanic activity related to the long‐standing continental convergence. The volcanoes of Armenia provide a rare opportunity to study the sources and processes involved in this unusual type of magmatism. More than 500 Quaternary volcanoes have been mapped in Armenia, most of them formed from single eruptive episodes. Among several large composite volcanoes, the mighty Aragats stands out as the largest volcano in Armenia and the region altogether. Volcanic deposits testify to the range of eruptive styles—from the ignimbrites formed in eruptions as explosive and voluminous as any seen globally in the modern era to the enormous fissure‐fed lava flows that form the Southern Caucasus flood basalt province, the smallest and youngest Large Igneous Province in the world. Several pre‐historical and historical eruptions have been documented, highlighting the potential for future volcanic activity in the region. In recent years, research has focused on the volcanic hazards associated with the Armenian Nuclear Power Plant, located in the foothills of Aragats volcano. This article highlights some of the extraordinary volcanic and intrusive features observed in Armenia and summarizes aspects of recent volcanological and petrological research.